Synthesis and Spectral Study of New Guanine Derivative (N-((6-Oxo-6,9-Dihydro-1H-Purin-2-yl)Carbamothioyl)Propionamide) and its Complexes with Some Metals Ion - Sh. Abdullah Alani, Abdullah; Muhsen Sarhan, Basima; Deepak Tripathi, Vishwa (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
This study included the preparation and characterization of the new guanine derivative (N-((6-oxo-6,9-dihydro-1H-purin-2-yl)carbamothioyl)propionamide), with an exciting chemical structure. The guanine part is a bicyclic heterocyclic base that is connected to a carbamothioyl group by a propionamide linker. This nitrogenous base derivative is prepared in two steps: The first step involves the synthesis of propionyl isothiocyanate from the reaction of propionyl chloride with ammonium thiocyanate in acetone. In contrast, the second step consists of the reaction of ammonium thiocyanate with guanine to obtain the ligand. The study also includes the preparation of new complexes of metal ions (Mn+2, Co+2, Ni+2, Cu+2, Zn+2, Cd+2, and Pd+2)  with a prepared guanine derivative. The ligand and complexes were characterized by using infrared spectra, ultraviolet-visible spectra, 1H-N.M.R., 13C-N.M.R. spectra, and elemental analysis (C.H.N.S.): molar conductivity measurement, magnetic susceptibility, atomic absorption, and melting point. The results of these studies showed that general formulas for these complexes were given [MCl2(O.P.P.)2], M = (Mn+2, Co+2, Ni+2, Cu+2, Zn+2, Cd+2, and Pd+2). It was found that the geometric shape of all the prepared complexes was an octahedron.